Free movement of money in the European Union: The role of European Court of Justice in the formation of free movement of capital and payments - Natalia Białek; Arkadiusz Bazylko (e-Finanse: Financial Internet Quarterly, 2011)
Free movement of capital and payments is one of four fundamental principles, whose undisturbed operation is vital for proper functioning of the Common Market. In the first stage of the European Community, this freedom served a rather ancillary function, facilitating the full use of the freedom of movement of goods, people and services. It was as late as at the beginning of the 1990s that this principle was considerably liberalized. The treaty regulations concerning free movement of capital and payments changed. These regulations obtained the status of direct effectiveness, which means that natural and legal persons may invoke them in courts and domestic institutions. However, the most essential role in forming the principle of free movement of capital and payments was played by European Court of Justice, whose judgments contributed to its present shape and allowed practically full liberalization of free movement of cash. The aim of this article is to show the evolution of the free movement of capital and payments flow under the influence of changing treaty regulations and the judgments of European Court of Justice.
Keywords: K33; 330; free movement of capital; free movement of payments; European Court of Justice